2019
DOI: 10.3390/f10040351
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Planting Density on Soil Bulk Density, pH and Nutrients of Unthinned Chinese Fir Mature Stands in South Subtropical Region of China

Abstract: Chinese fir (Cunninghamia lanceolata (Lamb.) Hook) is a fast-growing evergreen conifer with high-quality timber and is an important reforestation and commercial tree species in southern China. Planting density affects the productivity of Chinese fir plantations. To study the effect of five different planting densities and soil depth on soil nutrient contents of a mature C. lanceolata plantation, the soil nutrient contents (soil depths 0–100 cm) of 36-year-old mature Chinese fir plantations under five different… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
15
2
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 30 publications
3
15
2
7
Order By: Relevance
“…Ikenganyia et al (2017) similarly reported that lower density of bambara groundnut plants led to higher available P at crop harvest. Gil (2009) and Duan et al (2019) found that higher plant densities decreased soil contents of plant nutrients including P. Considering that Ikenganyia et al (2017) and the present study share similar climate, and that the effect of plant density on soil fertility could be climate dependent (Duan et al, 2019), we deduce that wider spacing is a more sustainable option than narrower spacing for bambara groundnut in the study location.…”
Section: Main Effects Of Bambara Groundnut Variety Plant Spacing Andsupporting
confidence: 53%
“…Ikenganyia et al (2017) similarly reported that lower density of bambara groundnut plants led to higher available P at crop harvest. Gil (2009) and Duan et al (2019) found that higher plant densities decreased soil contents of plant nutrients including P. Considering that Ikenganyia et al (2017) and the present study share similar climate, and that the effect of plant density on soil fertility could be climate dependent (Duan et al, 2019), we deduce that wider spacing is a more sustainable option than narrower spacing for bambara groundnut in the study location.…”
Section: Main Effects Of Bambara Groundnut Variety Plant Spacing Andsupporting
confidence: 53%
“…The pure Pinus stand showed lower soil pH as well as throughfall compared to the Pinus stand with broadleaf trees in the understory. Soil acidification is a common process in coniferous forests [20]; however, acidification appears in the surface horizon of the mineral soil [13,21]. Thus, the soil of the pure Pinus stand would be kept acidic by the acidic throughfall after canopy leaching and proton exchange by base cation in sea salt.…”
Section: Succession Of Forestmentioning
confidence: 99%
“…Our research also confirms this characteristic (Tables 1 and 2). In addition, the research of Duan et al [49] showed that soil bulk density in the 0-10 cm soil layer is influenced by stand planting density. The thickness of the humus horizon along the studied slopes used for agricultural purposes depends mainly on the plowing depth, that normally ranges from to 31 cm, on average reaching to a depth of 26 cm.…”
Section: Resultsmentioning
confidence: 99%